Moralization of law, heavy-penaltyism, and retributive justice: a corpus-assisted study of legal consciousness on Chinese social media - Wang, Han (International journal of law, crime and justice, 2024)
Previous studies on legal consciousness have primarily focused on individual-level interactions with legal institutions or personnel. However, this perspective may overlook the indirect experiences that citizens gain through social media and the social normative consensus behind individual experiences. To address this gap, this study examined the shared legal consciousness expressed by citizens on a social media platform. Using corpus-assisted discourse analysis and sentiment analysis, we analyzed 284,792 danmu comments from the most popular legal channel on Bilibili in China. Our findings provide a contemporary perspective on legal consciousness in Chinese social media, uncovering three prevailing ideologies: moralization of law, heavy-penaltyism, and a predilection for retributive justice over restorative justice. Through our mixed-methods approach using big data, we demonstrate the potential for expanding research on legal consciousness. Our findings enable a deeper understanding of how legal consciousness is expressed and shared among citizens in the digital age.